Mainstreaming Statistics in the Poverty Reduction Strategy Approach to Provide for More Effective Technical Assistance : Some Experience at the IMF - Kibuka, Robin (IMF Working Papers; Working Paper ;, 2007)
The paper reviews the Poverty Reduction Strategy (PRS) approach and efforts to build institutional statistical capacity to permit evidence-based monitoring of the Poverty Reduction Strategy Papers (PRSPs). Integrating the PRS approach and statistical development strategies could provide significant synergies in improving the monitoring of the PRSP goals. Mainstreaming the statistical strategies in such development plans should enhance the national priority for statistical reforms and provide a basis for costing such reforms for their incorporation into the medium-term expenditure framework. The paper concludes that such an outcome is likely to facilitate funding for the implementation of these reforms and boost the effectiveness of statistical technical assistance.